Peran Program Pemberdayaan Masyarakat dalam Meningkatkan Kesejahteraan Sosial dan Kemandirian Ekonomi Masyarakat Pedesaan - Suwardi Yasri Sabari; Suparman; Nurwafikah Amirah Budi; Arif Efendi AS; Haerusman (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by the importance of community empowerment programs in improving social welfare and the economic independence of rural communities in Baraka District, Enrekang Regency. This study aimed to describe the role of community empowerment programs, the supporting and inhibiting factors, and their impact on the social welfare and economic independence of rural communities. This study employed a qualitative approach with a descriptive research design. The research was conducted in Baraka District, Enrekang Regency, from February to April 2026. The research informants consisted of 9 individuals, including sub-district officials, village officials, community empowerment program implementers, community leaders, and community members participating in the program. Informants were selected using purposive sampling and snowball sampling techniques. The data sources consisted of primary and secondary data. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, member checking, and prolonged observation. The results showed that community empowerment programs played an important role in improving skills, social participation, and the economic independence of rural communities. This study implies the importance of strengthening sustainable community empowerment programs through skills training and community business assistance.